ANALYSIS OF INCOME AND FEASIBILITY OF CORN FARMING IN OEBOLA VILLAGE, FATULEU SUBDISTRICT, KUPANG REGENCY - Matildis, Angelina; Adar, Damianus; Nainiti, Selfius P. N.; Nurwiana, Ida (Undana Press, 2025)
This study aimed to determine the income and feasibility of corn farming. The research location was selected using purposive sampling, namely Oebola Village, Fatuleu Subdistrict, Kupang Regency. Respondents were determined using a simple random sampling method involving 40 respondents. The data used in this study consisted of primary and secondary data. The analytical methods applied were: (1) income analysis to determine the income generated from corn farming in Oebola Village, Fatuleu Subdistrict, Kupang Regency; and (2) corn-farming feasibility analysis to determine the feasibility of corn farming in the same location. The results showed that the average income from corn farming in Oebola Village was IDR 2,856,737.50 per farmer, or IDR 4,552,569.70 per 0.64 ha of land. Meanwhile, the revenue obtained was IDR 3,809,375.00. The income earned by corn farmers remains relatively low compared with its potential income. Based on the feasibility analysis, the R/C ratio was 6.3; the break-even point (BEP) of production was 190.5 kg per farmer and 297.7 kg per hectare. Meanwhile, the BEP price was IDR 1,430.88 per kg per farmer and IDR 2,280.30 per kg per hectare. Based on the results of this analysis, it can be concluded that corn farming in Oebola Village is feasible to operate and profitable.